2014
DOI: 10.6035/clr.2014.13.9
|View full text |Cite
|
Sign up to set email alerts
|

Cómo recuerdan los pacientes la comunicación del diagnóstico. A propósito de quince testimonios relacionados con enfermedades poco frecuentes

Abstract: Cómo recuerdan los pacientes la comunicación del diagnóstico. A propósito de quince testimonios relacionados con enfermedades poco frecuentes How patients remember when they were given the diagnosis. About fifteen testimonies related to rare diseases s a m a n t h a r e q u e n a r o m e r o / j u a n m . a r c o s u r r u t i a / a n t o n i o m . b a ñ ó n h e r n á n d e z u n i v e r s i d a d d e a l m e r í a AbstrAct: Doctor-patient communication has led, in recent years, great interest among the health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…Of the twenty studies, four of them, or 20%, showed evidence focused only on patients diagnosed with an RD (Adams et al, 2018; Alarcón‐Ovalle et al, 2016; Christensen et al, 2017; Jensen et al, 2019), and 45%, nine studies of the total, reported only on relatives (Anderson et al, 2013; Bendixen & Houtrow, 2017; Cardinali et al, 2019; Custódio et al, 2018; Esteban et al, 2015; Germeni et al, 2018; Granero‐Molina et al, 2020; Lim et al, 2012; Zurynski et al, 2017). Then, four studies focused on both family members and patients with an RD, representing 20% (Behan et al, 2016; Esquivel‐Sada & Nguyen, 2018; Henderson et al, 2009; Requena et al, 2014), whereas only one study focused on RD experts (Blöß et al, 2017). One included patients, relatives and lawyers (Kesselheim et al, 2015), and one included patients, relatives, organisations and healthcare professionals related to RDs which represent 5% each (Lopes et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the twenty studies, four of them, or 20%, showed evidence focused only on patients diagnosed with an RD (Adams et al, 2018; Alarcón‐Ovalle et al, 2016; Christensen et al, 2017; Jensen et al, 2019), and 45%, nine studies of the total, reported only on relatives (Anderson et al, 2013; Bendixen & Houtrow, 2017; Cardinali et al, 2019; Custódio et al, 2018; Esteban et al, 2015; Germeni et al, 2018; Granero‐Molina et al, 2020; Lim et al, 2012; Zurynski et al, 2017). Then, four studies focused on both family members and patients with an RD, representing 20% (Behan et al, 2016; Esquivel‐Sada & Nguyen, 2018; Henderson et al, 2009; Requena et al, 2014), whereas only one study focused on RD experts (Blöß et al, 2017). One included patients, relatives and lawyers (Kesselheim et al, 2015), and one included patients, relatives, organisations and healthcare professionals related to RDs which represent 5% each (Lopes et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Qualitative studies ( n = 14) (Lim et al, 2012; Requena et al, 2014; Kesselheim et al, 2015; Alarcón‐Ovalle et al, 2016; Bendixen & Houtrow, 2017; Blöß et al, 2017; Christensen et al, 2017; Adams et al, 2018; Lopes et al, 2018; Esquivel‐Sada & Nguyen, 2018; Germeni et al, 2018; Cardinali et al, 2019; Jensen et al, 2019; Granero‐Molina et al, 2020). All studies were judged to have appropriately used the qualitative approach to answer the research question and to have adequately used the qualitative data collection methods to address the research question.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations